The Bethesda system for reporting of thyroid cytopathology and its category wise management - Gupta, Varun; Singh, Pooja (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Fine-needle aspiration cytology (FNAC) of thyroid is a rapid diagnostic test for thyroid nodules. The Bethesda system classifies thyroid FNAC into six categories. Each category is linked to a malignancy risk and has recommended clinical management. The aim of this study was to analyze the thyroid cytology smears by Bethesda system and to assess the frequency of various categories and to correlate it previous published studies. Category wise management is also discussed in detail. Methods: A total of 388 thyroid FNAC samples were examined from January 2017 to June 2018 in the Department of Pathology, in Medanta- The Medicity Gurugram. Results: A total of 388 cases were reported according to Bethesda system of reporting. Categories were as follows: I (14.69%), II (61.85%), III (11.34%), IV (2.57%), V (2.660%), VI (4.91%) nodules. Conclusions: The Bethesda System for reporting thyroid cytopathology proved to be an excellent reporting system and it puts clinician and the cytopathologist on the same page and easier to communicate regarding diagnosis.